PARTICULARITIES OF POWER DENSITY SPECTRUMS OF EEG IN CONDITIONS OF PHYSIOLOGICAL REST AND NEGATIVE EMOTIONAL ACTIVATION IN HEALTHY AND IN PATIENTS WITH BRONCHIAL ASTHMA - A.M. Mamed"yarov; L.S. Namazova; L.M. Kuzenkova; N.Yu. Semenova; R.M. Torshkhoeva (Педиатрическая фармакология, 2008)
The article presents the results of the investigation of indices of power density spectrums of EEG in healthy and in patients with bronchial asthma in condition of physiological rest and negative emotional activation. The findings of this research about the disorganization of electrobiological activity of brain in patients with bronchial asthma show on the increased tonic activation of the brain controlling systems during this disease.Key words: bronchial asthma, EEG, emotional activation, power density spectrum, children.